(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
When designing or reconstructing buildings and structures on the swelling soils, it is necessary to be particularly concerned about the pattern of these soils behavior in order to subsequently be able to predict the behavior of the ‘basement – foundation – building’ system. The most effective way to stabilize soil behavior of the basement contaminated with industrial effluents is injection methods used for stabilization. The main task of soil chemical stabilization is to strengthen the bonds between soil particles with the help of chemical reagents. As a result of the research, the design parameters for foundations stabilization of soils composed contaminated with peroxy acid were determined. Depending on the concentration of peroxy acid in the soil and the density of the used sodium silicate solution, the limiting values initial components volume ratios were determined to carry out qualitative and reliable soil stabilization for the basements.